Study on Photodegradation of 4,4’-Dibromobiphenyl by TiO2 Films - Zhang, Ping; Ji, Caihong; Han, Pingfang (Asian Journal of Chemistry, 2010)
The TiO2 film photodegradation of 4,4'-dibromobiphenyl (4,4'-DBB) have been investigated by employing a UV lamp (8 W). Hydrogen peroxide and initial 4,4'-DBB concentrations, initial pH and possible reaction intermediates were also determined. The mechanism of photocatalytic degradation of 4,4'-DBB by TiO2 thin film was discussed. The dynamics of photocatalytic degradation of 4,4'-DBB was also studied. The results indicate that the 4,4'-DBB degradation rate decreased with the increase of initial 4,4'-DBB concentration under the same conditions. The degra-dation rate of 0.5 g/L 4,4'-DBB was 90 % within 4 h. In contrast to the results of the studies on other organic compounds, the optimum pH for degradation of 4,4'-DBB was 11. The removal efficiency was higher under alkaline conditions than acidic conditions. The principal products of 4,4'-DBB decomposition was 4-monobromobiphenyl, biphenyl and benzene derivatives. The reaction of photocatalytic degradation of 4,4'-DBB by TiO2 thin film followed a pseudo first-order kinetics, the reaction rate constant also decreased with the increase of initial 4,4'-DBB concen-tration.